Competency profile of university professors and their impact on future healthcare professionals - Villacís, Doménica D.; Defas, Nahin I.; Farfán, Henry A.; Silva, Jessica E.; Rosado, Kelly L. (Revista Gregoriana de Ciencias de la Salud, 2025)
The expectations of a student entering health-related careers are high; the quality of these future professionals depends on the teacher, who is more than an instructor — they are a mentor and guide. A qualitative and descriptive literature review was conducted on the main competencies of faculty in the Health Sciences. Key phrases were used in academic search engines, and 50 articles published between 2000 and 2025 were selected. The fundamental competencies included disciplinary knowledge, pedagogical skills, communication, cultural and sociological understanding, empathy, ethics, adaptability, digital literacy, and language proficiency. The specific competencies encompassed technology integration, research and development, clinical mentoring, clinical simulation, assessment and feedback, continuous growth, and curriculum internationalization. Faculty preparation in the Health Sciences must adapt to a changing academic and professional environment, emphasizing research, collaborative, and ethical competencies in line with the needs of the society in which the future professional will be integrated.